Pilot for the Implementation of a Registry for Endovascular Repair of Infrarenal Aortic Aneurysm Colombia – RREAC (2025)
Background: Endovascular aneurysm repair (EVAR) is the optimal treatment for infrarenal aortic aneurysms, but Colombia lacks a standardized national registry to analyze procedural outcomes and adherence to best practices. The Registry for Endovascular Repair of Infrarenal Aortic Aneurysm in Colombia (RREAC) aims to evaluate the viability of the implementation of a national registry, the quality of data, compliance of physicians, and patient safety. Methods: This prospective pilot study was conducted in two high-volume facilities in Medellín, Colombia. The study consisted of two phases: (1) validation of 58 registry variables by 10 vascular surgery experts through a Delphi consensus, and (2) collection of clinical data from 40 patients who received EVAR from May to November 2024. Technical success, rates of complications, and vascular patency at 30 days and three months were primary outcomes. Results: The validation phase confirmed high content validity, with 54 of 58 variables (93.1%) showing an Aiken's V > 0.8. Four borderline variables—erosion of the stent graft through the vessel (0.78), identification (0.73), lymphatic fistula (0.72), and fever of unknown origin (0.74)—were retained following expert consensus. The clinical phase included 40 patients, with a 98% data completion rate. Mean age was 73.8 ± 6.5 years; 82.5% were male, and mean BMI was 23.9 ± 3.8. The most prevalent comorbid conditions were hypertension (67.5%), diabetes (27.5%), and smoking (20%). No patient had HIV or decompensated heart failure. Anatomically, mean neck length was 33.4 ± 12.2 mm, aneurysm diameter 60.8 ± 12.5 mm, and stent graft diameter 25.8 ± 3.23 mm, with oversizing of 18.3 ± 3.89%. Trimodular prostheses were used in 50%, iliac branch devices in 22.5%. Mean operating time was 139.7 ± 60 minutes, mean blood loss 225 mL (range 200–387 mL), with 10% requiring transfusion. Per cent percutaneous closure was successful in 67.5% of patients. Radiation time averaged 29.5 ± 21.5 minutes, contrast volume 103.4 ± 42.7 mL. Technical success was 95% (38/40), with two intraoperative complications: one rupture of an iliac artery requiring open repair and one type Ia endoleak. Postoperative complications occurred in 17.5% (7/40), primarily type II endoleaks (10%) and hematomas at the access site (15%). Thirty-day death was 2.5% (1/40). Patency at 30 days was 95% (38/40), and at three months, 97% (36/37). Secondary patency was 100% (37/37), excluding two lost to follow-up and one early death. Conclusion: The RREAC registry is technically possible and applicable as a venue for standardized EVAR outcome reporting in Colombia. This pilot phase underlines strong expert consensus on variable validity and has high technical success, low complication and mortality rates, and excellent early patency —comparable to international benchmarks— favoring wider national implementation.